Queen Charlotte - Quinn, Julia, 1970-; Rhimes, Shonda (Quinn, Julia, 1970- Bridgerton series., 2023)
"In 1761, on a sunny day in September, a King and Queen met for the very first time. They were married within hours. Born a German Princess, Charlotte of Mecklenburg-Strelitz was beautiful, headstrong, and fiercely intelligent--not precisely the attributes the British Court had been seeking in a spouse for the young King George III. But her fire and independence were exactly what she needed because George had secrets-- secrets with the potential to shake the very foundations of the monarchy. Thrust into her new role as a royal, Charlotte must learn to navigate the intricate politics of the court, all the while guarding her heart, because she is falling in love with the King, even as he pushes her away"--Dust jacket flap